Effect of Irrigation and Mulch on the Yield and Water Use of Strawberry - Rahena Parvin Rannu; Razu Ahmed; Alamgir Siddiky; Abu Saleh Md. Yousuf Ali; Khandakar Faisal Ibn Murad; Pijush Kanti Sarkar (International Journal of Agronomy)
To investigate the effect of irrigation and mulch on the yield of strawberry (line FA-007), this study was conducted at the experimental fields of Pomology Division, BARI, Gazipur and RARS, BARI, Rangpur during Rabi season of 2012-13 and 2013-14. The experiment was conducted followed by the split-plot design with two mulches (black plastic and rice straw), three levels of irrigation (5, 10, and 15 days interval), and three replications. A significant difference was observed for most of the parameters among different treatments for both locations. Irrigation at 5 days interval with rice straw mulch in Gazipur and irrigation at 5 days interval with black polythene mulch in Rangpur were performed better for most of the yield-contributing characters and yield among all other treatments for both the years. But in respect to water productivity, 10 days irrigation interval with rice straw mulch in Gazipur and 10 days interval with black polythene mulch in Rangpur showed highest results among all other treatments. However, it can be concluded that any irrigation practices from the abovementioned options could be adopted by the farmers based on their feasibility and water availability for strawberry cultivation in Bangladesh.